2016
DOI: 10.1177/1948550615626776
|View full text |Cite
|
Sign up to set email alerts
|

Instilling Hope for Peace During Intractable Conflicts

Abstract: A set of studies explored the possibility to instill hope for peace in the context of intractable conflicts. The first study examined Jewish-Israelis’ hopes for peace following a message from an out-group communicator. Results show that participants’ hopes increased after viewing a Palestinian conclude that the conflict was solvable. This held true regardless of whether the Palestinian communicator identified as a militant or a peace activist. However, Jewish-Israelis’ hopes for peace were not altered when an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…According to research with people who are involved in seemingly intractable conflicts, hope is associated with decreased dehumanization of (Halperin et al, 2008) and increased support for humanitarian aid provided to (Halperin & Gross, 2011)out-group members, and it is also associated with reduced desire for retaliation (Moeschberger et al, 2005) and increased desire for reconciliation (Cohen-Chen et al, 2019;Rosler, Cohen-Chen, & Halperin, 2015). Importantly, experimental studies have demonstrated that exposure to information about the outgroup's judgments can facilitate intergroup openness, at least to the extent that it increases hope (Leshem, Klar, & Flores, 2016;Saguy & Halperin, 2014).…”
Section: The Affective Routementioning
confidence: 99%
“…According to research with people who are involved in seemingly intractable conflicts, hope is associated with decreased dehumanization of (Halperin et al, 2008) and increased support for humanitarian aid provided to (Halperin & Gross, 2011)out-group members, and it is also associated with reduced desire for retaliation (Moeschberger et al, 2005) and increased desire for reconciliation (Cohen-Chen et al, 2019;Rosler, Cohen-Chen, & Halperin, 2015). Importantly, experimental studies have demonstrated that exposure to information about the outgroup's judgments can facilitate intergroup openness, at least to the extent that it increases hope (Leshem, Klar, & Flores, 2016;Saguy & Halperin, 2014).…”
Section: The Affective Routementioning
confidence: 99%
“…It is increasingly clear that emotional expressions play an important role in the regulation of intergroup relations (De Vos, van Zomeren, Gordijn, & Postmes, 2013;Goldenberg, Saguy, & Halperin, 2014;Kamans, van Zomeren, Gordijn, & Postmes, 2014;Nadler & Liviatan, 2006;Solak, Reifen, Cohen-Chen, Saguy, & Halperin, 2017;Van Kleef, Steinel, & Homan, 2013;Wohl, Hornsey, & Bennett, 2012). With regard to hope in particular, recent work has investigated effects of hope expressions by outgroup members (Leshem et al, 2016) or the outgroup as a whole on experienced hope and concession-making in conflict. However, research has yet to explore how expressions of hope made by ingroup members to their own group influence attitudes regarding intergroup conflict.…”
Section: Emotional Expressions In Intergroup Conflict: the Role Of Pomentioning
confidence: 99%
“…In intergroup conflict, and especially intractable conflict (Bar-Tal, 2013;Coleman, 2011;Kelman, 2007;Kriesberg, 1993), hope has been found to be associated with positive intergroup attitudes (Halperin, Bar-Tal, Nets-Zehngut, & Drori, 2008;Lala et al, 2014), concession-making (Rosler, Cohen-Chen, & Halperin, 2017), willingness to provide humanitarian aid (Halperin & Gross, 2011), processing of conciliatory information (Cohen-Chen, Halperin, Porat, & Bar-Tal, 2014), and forgiveness (Moeschberger, Dixon, Niens, & Cairns, 2005). Recently, experimentally induced hope has been shown to increase attitude-change (Cohen-Chen, Halperin, Crisp, & Gross, 2014;Cohen-Chen, Crisp, & Halperin, 2015;Leshem, Klar, & Flores, 2016;, establishing experiencing hope as an important factor driving attitudechange in conflict resolution processes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mindfully attending to a counterpart's expression of hope that the situation can improve could promote helpful reciprocal attitudes from the perceiver around compromising or creatively resolving conflict. Specifically, experiencing hope, a futureoriented emotion which enables imagining a better future (Stotland, 1969), has been shown to successfully promote compromise in conflict (Cohen-Chen, Crisp, & Halperin, 2015;Cohen-Chen, Halperin, Crisp, & Gross, 2014;Saguy & Halperin, 2014) and out-group expression of hope is associated with a willingness to make concessions in conflict situations (Cohen-Chen, Crisp, & Halperin, 2017;Leshem, Klar, & Flores, 2016).…”
Section: Mindfulness Of Emotion As Both Detrimental and Beneficialmentioning
confidence: 99%